Nutritional Health Education during Pandemic - Dewi, Novita; Metrikayanto, Wahyu Dini; Supriyadi (Journal of Community Service for Health, 2021)
Covid-19 has been booming since December 2019, and is a serious concern in the world. The transmission of this virus is very fast, especially in patients who are hospitalized. So that as a precautionary measure of contracting this virus, actions can be taken in the form of enlightenment in terms of cognitive to the community, in this case in the form of Educational Interactive Communication in the form of Health Education. Health education for patients to meet adequate nutritional intake, so that it is hoped that the spread of this virus can be inhibited with high immunity obtained from varied, balanced nutrition, and all aspects of substances that the body needs can be fulfilled. The purpose of this community service is to provide health education to 15 patients. The method provided is in the form of service learning by providing health education to patients by visiting the patient one by one at each patient. The results of this community service were all participants who understand about nutritional intake, types of balanced nutrition, and things that increase immunity in preventing the transmission of covid-19